A Critical Study of Abdul Rahman Al Kawakibi’s Social Thought - Ahmed, Osman Sirajeldeen (International Journal of Psychosocial Rehabilitation, 2020)
The Study objective provides a critical view of the social thought of the Islamic thinker Abdul Rahman Al-Kawakibi, especially those ideas that were mention of in the most important books of Umm Al-Qura, / The Tyranny and the Nature of enslavement. The criticisms levelled are limited to the social side of the AlKawakibi’s intellectual issues, which have played a big role in his thought, and the monetary issues that are discussed such as the Islamic Nation, social utopia and populism, social elite, the status of women, social work, freedom and tyranny.